Tacit knowledge awareness and sharing influence on innovation - Wioleta Kucharska; G. Scott Erickson (Gdańsk University of Technology, Faculty of Management and Economics, 2021)
This study measures the relationship between tacit knowledge and innovation in the Polish and US information technology (IT) industries. Large samples were obtained, allowing quantitative modeling not possible in many tacit knowledge studies focused on more qualitative analysis. Conceptually, the study identifies the potential sources of tacit knowledge (learning-by-doing and/or learning-by-interaction), individual tacit knowledge development leading to a willingness to share, and the consequent correlation to process and/or product/service innovation. The important role of critical thinking as a control variable in tacit knowledge development in individuals is also identified as is the connection of process innovation as a mediator between tacit knowledge sharing and product/service innovation.The model is supported across both samples though with interesting differences across countries, particularly in sources of tacit knowledge (more learn-by-doing in the US), the link between awareness and sharing (stronger in US), and innovation (process as a full mediator in Poland, complementary in the US). The main theoretical contribution is empirical support for tacit knowledge's role in innovation, including the step-by-step details of how everything connectsas well as details on how the model can differ by national context. The managerial implications include the care that must be taken to evaluate national circumstances and their potential impact on a firm's management of tacit knowledge.
Keywords: 330; Tacit knowledge; knowledge awareness; knowledge sharing; innovation; IT industry; Poland; USA